Pharmacological Treatment of Interstitial Lung Diseases: A Novel Landscape for Inhaled Agents - Vito D’Agnano; Fabio Perrotta; Ramona Fomez; Valerio Maria Carrozzo; Angela Schiattarella; Stefano Sanduzzi Zamparelli; Raffaella Pagliaro; Andrea Bianco; Domenica Francesca Mariniello (Pharmaceutics)
Interstitial lung diseases (ILDs) encompass a heterogeneous group of over 200 disorders that require individualized treatment. Antifibrotic agents, such as nintedanib and pirfenidone, have remarkably revolutionized the treatment landscape of patients with idiopathic pulmonary fibrosis (IPF). Moreover, the approval of nintedanib has also expanded the therapeutic options for patients with progressive pulmonary fibrosis other than IPF. However, despite recent advances, current therapeutic strategies based on antifibrotic agents and/or immunomodulation are associated with non-negligible side effects. Therefore, several studies have explored the inhalation route aiming to spread higher local concentrations while limiting systemic toxicity. In this review, we examined the currently available literature about preclinical and clinical studies testing the efficacy and safety of inhalation-based antifibrotics, immunomodulatory agents, antioxidants, mucolytics, bronchodilators, and vasodilator agents in ILDs.